Robust nonlinear sliding mode controllers for single-phase inverter interfaced distributed energy resources based on super twisting algorithms. (April 2022) - Barzegar-Kalashani, Mostafa; Tousi, Behrouz; Mahmud, Md. Apel; Farhadi-Kangarlu, Mohammad
Abstract: This paper presents a voltage control mode (VCM)-based super-twisting algorithm-sliding mode controller (STA-SMC) and current control mode (CCM)-based STA-SMC for islanded and grid-connected operations of single-phase inverters interfaced with distributed energy resources (DERs), respectively. The external disturbances are modeled by considering the effects of load currents or load voltages depending on operational modes whiles parametric uncertainties are modeled based on their variations from nominal values. Therefore, the proposed controllers are robust against external disturbances, parametric uncertainties, and variations in loading conditions. Simulation studies are conducted in the MATLAB/Simulink platform for both single and multiple DERs which are interfaced through single-phase inverters to the main grid or loads. The results are also analyzed through comparative studies with different controllers and it is found that the proposed controllers perform better than existing controllers. Highlights: A VCM-based STA-SMC is designed for islanded operations of DERs. A CCM- STA-SMC is designed for grid-connected operations of DERs. The robustness is analyzed against external disturbances and parametric uncertainties. Performances are evaluated under different loading conditions.